Penilaian Risiko K3 Menggunakan JSA Pada Pengrajin Emas Kelurahan Rappokalling Kota Makassar - Qidam, Zultansur Ali; Abbas, Hasriwani Habo; Hardi, Ikhram (Window of Public Health Journal, 2025)
According to global estimation data released by the International Labor Organization (ILO) in 2017, every year as many as 2.78 million workers die due to workplace accidents and work-related diseases. Among them, 2.4 million workers (86.3%) died related to work-related diseases and 380,000 workers (13.7%) died due to work accidents. This case shows an overall increase in the number of deaths due to work, namely in 2014 the death rate was 2.33 million, up in 2017 to 2.78 million deaths. The purpose of this study was to determine the risk value at each stage of the goldsmith's work in Rappokalling Village, Tallo District, Makassar City in 2022. The research method used is descriptive with an observational approach where this research makes a systematic, factual and accurate description of the facts and characteristics the nature of the risk in gold craftsmen through observation and no treatment of the research object during the study. This study uses Job Safety Analysis (JSA) as a reference in assessing occupational health and safety risks. In all work stages there are 3 which are included in the very high category, 2 work stages are included in Priority 1, 6 stages are included in the Substantial category, 1 each stage is included in the Priority 3 and acceptable categories.